The Performance Optimization of the Turjawali Unit Through Patrols by the Crime Prevention Unit of Sragen Police Resort in Order to Minimize Motor Vehicle Theft - Wibowo, Lukman (Advances in Police Science Research Journal, 2024)
Sragen Regency is a region that has a dense population. This population is the background of the increasing crime of motor vehicle theft after this covid-19 pandemic. Even though the number of criminal acts of motor vehicle theft was high in 2020, 52 cases, the number of criminal acts of motor vehicle theft decreased in 2021 due to Covid-19. In the following year, the number of motor vehicle theft crimes began to rise again with the number of motor vehicle theft crimes reaching 64 cases in the last two years. This final project writing aims to explain how the organizational and systematic resources of the Turjawali unit of Crime Prevention Unit of Sragen Police Resort in order to minimize the crime of motor vehicle theft. The research was conducted using qualitative and data collection techniques through observations, interviews and document studies. This writing uses two theories as a knife analysis of existing problems. The theories used are the theory of organizational resources and the theory of management. Furthermore, to discuss the factors that influence the performance of the Turjawali unit of Crime Prevention Unit of Sragen Police Resort in carrying out patrols, the writer uses the SWOT theory. The concepts used in this writing are the concept of Optimization, the concept of Performance, the concept of Patrol and the concept of motor vehicle theft. The results of the research on this final project are the efforts made by the turjawali unit of satsamapta Polres Sragen in reducing the crime of theft of motorized vehicles is still not optimal. There are still shortcomings found, starting from the organizational resources of Man, Money, Material, and Method. Then there are also shortcomings in the systematics works of the Turjawali unit, namely from Planning, Organizing, actuating, and controlling. Based on the observations made by the writer, the Turjawali unit of Crime Prevention Unit of Sragen Police Resort must optimize the performance of the Turjawali unit in carrying out patrols using the suggestions given by the writer. So, in carrying out patrols, the Turjawali unit of Crime Prevention Unit of Sragen Police Resort can run optimally and can minimize criminal acts of motor vehicle theft.